Analysis of Biosecurity Application in Broiler Chicken Farms in North Sumatra - Ma'ruf Tafsin; Nevy Diana Hanafi; Achmad Sadeli; Tuty Elvi Farida (Indonesian Journal of Agricultural Research, 2023)
Biosecurity is very important in broiler chicken farming. The right biosecurity application will create optimal performance. This research was conducted in three districts of North Sumatra province, namely Deli Serdang, Serdang Bedagai and Simalungun with purposive sampling methods. Number of samples used by 104 respondents. This research was conducted to find out the level of application of biosecurity and health conditions in the maintenance of modern broiler chickens. The data used in the study used primary data obtained from filling out questionnaires and discussions with farmers. The parameters used use the Likert scale with integers of 1, 2, 3, 4, and 5 for each answer. There are three categories in the application of biosecurity, namely pre of entry, point of entry and post of entry. Disease conditions that often appear during the maintenance of broiler chickens related to the performance obtained by respondents. The results of the statistical analysis illustrate that the level of application of pre-entry biosecurity (P<0.05) describes 67% of the significant results of 6 questions, the point of entry (P<0.05) shows 100% insignificant results from 6 questions and post of entry (P<0.05) shows 43% significant results from 7 questions on closed house and open house systems. The results of data obtained from cases of diseases that are often a problem in broiler chickens more cases of enteritis (digestive) disease by 27.9% and CRD by 25% of the total respondents.